BIMBINGAN DAN PELATIHAN SENI MELUKIS KACA BAGI ANGGOTA PKK RT. 2 RW. 7 KELURAHAN JATIMULYO KEC. LOWOKWARU MALANG - Ellyn Eka Wahyu (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
Education is a human need that gets great attention in the community, because education can make people develop into individuals who have knowledge, attitudes and skills that can support life in the community, and able to face the times. Education is an important capital in the progress of a nation, therefore education is a major concern in the life of the community from small environmental community ie family to the great environment of the nation, the realization of the goals and functions of national education above, pursued and implemented through formal education, informal and non-formal. Non-formal education is an education held outside the school educational institution dedicated to citizens who need educational services. The function of non-formal education is as a substitute, adder, and or to complete formal education, in meeting the needs with various skills and mastery of functional knowledge and the development of professional attitude and personality. The problems that arise in this era of globalization, especially the increasingly limited job opportunities and increased unemployment from year to year. This unemployment problem needs immediate attention from various parties. One of the training that can provide knowledge and skill for them in the readiness of entrepreneurship is the training of glass painting. One of the goals and benefits of this activity is to provide new insight to the community that the art of painting glass can create an independent craft business and is expected to benefit the trainees that the results of glass painting training is expected to be a source of knowledge, attitude and skills in readiness to open and develop a craft business. After carrying out this Community Service activity, to see its success, it can be seen from the desire of the participants to be able to further develop these skills as a side business to supplement family income (because by painting on glass media, can add 'product value' so that when sold will be more expensive because of the beauty of the painting), and is also used to further beautify household appliances made from glass is more beautiful and has a higher artistic value if used alone.